1995
DOI: 10.1007/bf01745530
|View full text |Cite
|
Sign up to set email alerts
|

Theory for the atomic shell structure of the cluster magnetic moment and magnetoresistance of a cluster ensemble

Abstract: Abstract. We present a simple theory for the cluster size dependence of the average cluster magnetic moment of transition metal clusters. Assuming a local environmental dependence of the atomic magnetic moments, the cluster magnetization exhibits a magnetic shell structure, reflecting the atomic structure of the cluster. Thus, the observed oscillations of the average cluster magnet moment may serve as a fingerprint of the cluster geometry. We also discuss the giant magnetoresistance (GMR) exhibited by an ensem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 14 publications
6
43
0
Order By: Relevance
“…41a, b) [640,644] and the inconsistent trends of M S measured at different temperature ranges. Several shell structural models have been proposed for the size-enhanced magnetization [644,661] and suggested that the magnetic moment of an individual atom is determined by its atomic CN [661]. By assuming bulk-like structures (such as fcc and bcc) and different global cluster shapes (cube, octahedron, cube octahedron), the average magnetic moment was found to oscillate with the cluster size, coinciding with observations.…”
Section: Discussionsupporting
confidence: 68%
“…41a, b) [640,644] and the inconsistent trends of M S measured at different temperature ranges. Several shell structural models have been proposed for the size-enhanced magnetization [644,661] and suggested that the magnetic moment of an individual atom is determined by its atomic CN [661]. By assuming bulk-like structures (such as fcc and bcc) and different global cluster shapes (cube, octahedron, cube octahedron), the average magnetic moment was found to oscillate with the cluster size, coinciding with observations.…”
Section: Discussionsupporting
confidence: 68%
“…19.1a, b) [21,25] and the inconsistent trends of M S measured at different temperature ranges. Several shell structural models have been proposed for the size-enhanced magnetization [25,45] which suggested that the magnetic moment of an individual atom is determined by its atomic CN [45]. By assuming bulk-like structures (such as fcc and bcc) and different global cluster shapes (cube, octahedron, and cube octahedron), the average magnetic moment was found to oscillate with the cluster size, agreeing with observations.…”
Section: Magnetizationsupporting
confidence: 69%
“…Assuming a completely different point of view than Fujima and Sakurai by disregarding the electronic effects, Jensen and Bennemann 17 have developed a simple geometrical theory for the atomic shell structure of . They have assumed that the magnetic moment of a specific atomic site is a monotonic function of the coordination number (z), the former being lower for closed atomic shells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ab initio calculations do not give support to certain hypotheses like the integer and invariant number of d and s electrons per atom used in the model of Fujima and Sakurai 16 or the monotonic behavior of versus z used in the model of Jensen and Bennemann. 17 Recently, semiempirical electronic structure calculations of freestanding TM clusters have been performed by different groups using a bulk parametrized spd tight-binding Hamiltonian. 14,15,18,19 These semiempirical models lead to good qualitative agreement with the experiments when the parametrization is good and when they are solved selfconsistently.…”
Section: Introductionmentioning
confidence: 99%